2020
DOI: 10.3390/molecules25122833
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Herbage Yield, Antioxidant Activities, Phytochemical Contents, and Bioactive Compounds of Sabah Snake Grass (Clinacanthus Nutans L.) with Regards to Harvesting Age and Harvesting Frequency

Abstract: Sabah snake grass or Clinacanthus nutans has drawn public interest having significant economic benefits attributable to the presence of phytochemicals and several interesting bioactive constituents that may differ according to harvesting age and harvesting frequency. The current study was aimed to evaluate the effect of harvesting age and harvesting frequency towards herbal yield, antioxidant activities, phytochemicals synthesis, and bioactive compounds of C. nutans. A factorial randomized completely block des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Over the past several years, medicinal plants have gained greater attention and recognition in Malaysia, particularly as demand for alternative medicine and natural health products increases in 2019 [1,2]. A total of 351 hectares of Malaysian land has yielded 1317 metric tonnes of herbs in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years, medicinal plants have gained greater attention and recognition in Malaysia, particularly as demand for alternative medicine and natural health products increases in 2019 [1,2]. A total of 351 hectares of Malaysian land has yielded 1317 metric tonnes of herbs in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of plant part, our study was similar to Quah et al [ 41 ] that used CN leaves, however, Mutazah et al [ 40 ] used bark to prepare CN methanolic extract. Other than that, previous study reported that the harvesting age and harvesting frequencies may influence the phytochemical content in CN plant especially shaftoside, isoorientin and orientin [ 44 ]. The highest total phenolic content and flavonoids can be obtained from harvesting at week 16 during first harvest.…”
Section: Discussionmentioning
confidence: 99%
“…Other factor that might explained the difference of the antiproliferative activity of CN was that there might be variation in the amount of phytochemical content in various CN extracts. According to a study, phytochemical production in CN plant was high until 6 months of age and decreased until reaching one year of age [ 45 ] and increased harvesting frequency results in decreased amount of total phenolic and flavonoids contents in CN plant [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These positive correlations mirrored those found in Manivannan et al’s [ 42 ] study, which found a strong positive correlation between the total phenol, flavonoid content, and antioxidant content of tissue extracts. As cancer prevention agents and also for other human disorders, phenolic compounds and flavonoids are applied to the vast majority of organic compounds in higher plants, including medicinal and officinal plants [ 60 ]. A positive correlation between antioxidant activity and phenolic content has also been reported in other studies [ 32 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%